Rozwój technologii informatycznych a zmiany w projektowaniu i prowadzeniu badań marketingowych - Prokopiuk, Jerzy; Pachnowska, Beata (Information Technologies Development Versus Changes in Designing and Carrying Aut Marketing Research, 2006)
The authors point to a significant influence of the new technologies (mainly the development of telecommunication and Internet) on the changes in market research. Amongst the results of that change they mention e.g. the introduction of new methodologies (on-line research, CAPI), shortening of the turnaround time of the research projects, centralised co-ordination of research as well as the way of communication within the market research industry. The authors try to predict the development of market research in Poland in the coming years based on some remarkable trends in the United States and western Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 607-614